2021
DOI: 10.46245/ijorer.v2i2.91
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Training in Pakistan: Overview of Challenges and their Suggested Solutions

Abstract: Education is a key component of progress in the present-day world. But this progress cannot be made without efforts of teachers. Therefore, teacher education, in particular teacher training becomes extremely important. In this regard, several trainings programs are initiated and executed across Pakistan but the desired outcomes have not been achieved so far. Hence, this study was conducted to explore the challenges in teacher training in Pakistan and the ways through which these issues can be resolved. The sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Among many studies in educational leadership in Sindh, Rizvi (2010) explored that proper EL improves the quality of their local education systems through increasing the diversity of application of their programs. Along with many bureaucratic and financial challenges, educational leaders also come across with lack of resources and training opportunities (Siddiqui et al, 2021). Like all other provinces, the majority of educational leaders in Sindh also believe that the job of an educational leader is to deal with financial matters and correspondence with high officials.…”
Section: Educational Leadership In Sindhmentioning
confidence: 99%
“…Among many studies in educational leadership in Sindh, Rizvi (2010) explored that proper EL improves the quality of their local education systems through increasing the diversity of application of their programs. Along with many bureaucratic and financial challenges, educational leaders also come across with lack of resources and training opportunities (Siddiqui et al, 2021). Like all other provinces, the majority of educational leaders in Sindh also believe that the job of an educational leader is to deal with financial matters and correspondence with high officials.…”
Section: Educational Leadership In Sindhmentioning
confidence: 99%
“…Furthermore, Dayan et al (2018) reported that one of the challenges in teacher education in Pakistan is the gap between the training theory and actual practice in the classroom, and that teachers are unable to manage conflictual behavior in the classroom even after participating in professional development programs. Other issues were reported by Siddiqui et al (2021a) include that, in addition to financial constraints, teacher education institutes lack facilities such as teaching aids, buildings, libraries, furniture, teaching materials, and other supplies. Poor management and inefficient administration are also among the most frequently cited problems (Azam et al, 2014).…”
Section: Challenges Related To Teacher Professional Development In Pa...mentioning
confidence: 99%
“…As various teachers differ in performances, it has become a challenge for policymakers and school leaders to design PD programs to help all their teachers become as effective as the best teachers (Sims et al, 2021). Several training programs were initiated and executed across Pakistan but failed to achieve the desired outcome (Siddiqui et al, 2021). There is a need of systematizing professional training programs and their continuation (Arif et al, 2022).…”
Section: Introductionmentioning
confidence: 99%